The Effect of Job Satisfaction and Motivation on the Performance of Employees of the Pasasi Division of PT Sriwijaya Air Cengkareng District During the Pandemic in 2022 - Husni Hasan; Aswanti Setyawati; Sandriana Marina; Rohana Sitanggang; Aisyah Rahmawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of research is to determine the effect of job satisfaction (X1) and motivation (X2) on the performance (Y) of employees of the Pasasi Division of PT Sriwijaya Air, Cengkareng District in the Pandemic Period in 2022. The problems that exist in this research are that many employees of PT. Sriwijaya Air are laid off and laid off, the salaries that employees receive have decreased by 20%, Jobdesk employees have increased so that they are less motivated to work. The methods used in this study are quantitative methods and collection techniques. The data consists of observations, questionnaires via google form and literature study. In this study using a non-probability sampling technique with a total census/sampling method as many as 39 respondents. The data analysis technique used is data instrument test, descriptive analysis, classical assumption test, hypothesis testing, multiple linear regression analysis test, multiple correlation analysis and coefficient of determination analysis and processed using SPSS version 26 application. The correlation results show job satisfaction and motivation variables. has a very strong influence (0.919) on performance. The results showed that job satisfaction and motivation had a significant and positive effect on performance. The managerial implication in this study is